Plant-associated Toxins Agricultural, Phytochemical, and Ecological Aspects - Colegate, Steven M; Ed (CAB International, 1994)
This text represents the proceedings of the 4th International Symposium on Poisonous Plants which was convened in Fremantle, Western Australia in September 1993. The research addresses all aspects of plant-associated toxins with relevance to human and animal health and medical research.